A novel integrated dual microneedle-microfluidic impedance flow cytometry for cells detection in suspensions - Muhammad Asraf Mansor; Masaru Takeuchi; Masahiro Nakajima; Yasuhisa Hasegawa; Mohd Ridzuan Ahmad (Institute of Advanced Engineering and Science, 2017)
In this study, a new, simple and cost-effective impedance detection of yeast cell concentration by using a novel integrated dual microneedle-microfluidic impedance flow cytometry was introduced. The reported method for impedance flow cytometry detection utilizes embedded electrode and probe in the microfluidic device to perform measurement of electrical impedance when a presence of cells at sensing area. Nonetheless, this method requires costly and complicatedly fabrication process of electrode. Furthermore, to reuse the fabricated electrode, it also requires intensive and tedious cleaning process. Due to that, a dual microneedle integrated at the half height of the microchannel for cell detection as well as for electrical measurement was demonstrated. A commercial available Tungsten needle was utilized as a dual microneedle. The microneedle was easy to be removed from the disposable PDMS microchannel and can be reused with the simple cleaning process, such as washed by using ultrasonic cleaning. Although this device was low cost, it preserves the core functionality of the sensor, which is capable of detecting the passing cells at sensing area. Therefore, this device is suitable for low cost medical and food safety screening and testing process in developing countries.